Human Stress Detection: Cortisol Levels in Stressed Speakers Predict Voice-Based Judgments of Stress. (January 2021) - Pisanski, Katarzyna; Sorokowski, Piotr
Despite recent evidence of a positive relationship between cortisol levels and voice pitch in stressed speakers, the extent to which human listeners can reliably judge stress from the voice remains unknown. Here, we tested whether voice-based judgments of stress co-vary with the free cortisol levels and vocal parameters of speakers recorded in a real-life stressful situation (oral examination) and baseline (2 weeks prior). Hormone and acoustic analyses indicated elevated salivary cortisol levels and corresponding changes in voice pitch, vocal tract resonances (formants), and speed of speech during stress. In turn, listeners' stress ratings correlated significantly with speakers' cortisol levels. Higher pitched voices were consistently perceived as more stressed; however, the influence of formant frequencies, vocal perturbation and noise parameters on stress ratings varied across contexts, suggesting that listeners utilize different strategies when assessing calm versus stressed speech. These results indicate that nonverbal vocal cues can convey honest information about a speaker's underlying physiological level of stress that listeners can, to some extent, detect and utilize, while underscoring the necessity to control for individual differences in the biological stress response.